If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8t + (-3t) = 15 Combine like terms: 8t + (-3t) = 5t 5t = 15 Solving 5t = 15 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Divide each side by '5'. t = 3 Simplifying t = 3
| -8x^2+6xy+3y^2+10x=0 | | 1/4-2/3=2/5-8/3 | | e^5x/4e^2 | | 4.28-0.4d=6 | | 9v+6=10v-3 | | 3m+34=16 | | 40+0.25x= | | 4.28-0.4d=2.28 | | 3c+5=2c+14 | | 4x^2+4y^2-40x+16y+104=0 | | m/2+4=10 | | 5x+8=47 | | 5x+2x=5 | | Y^2+10y-264=0 | | -33-5x=8x+19 | | x(x-6)+x^2=(x-5)(x+2) | | 18x^2=6x | | 3/4+3/10 | | 36y=30y^2 | | 105=5(8+b) | | -10=-4+2x | | 3n+4=27n | | 4k-8-6k=6+5k | | 3n+4=272n | | 63y=30y | | 3xy+2xy= | | 5(13+y)-3y=10 | | x^2-7-x-5=0 | | =D | | 5(13+y)-y=18 | | x+2=17+x | | 2a+5=6a+5 |